STUDI DAN PEMANFAATAN GELOMBANG SUARA DALAM KEHIDUPAN SEHARI-HARI DI PULAU TIDUNG - Kasiah (Universitas Nias Raya, 2023)
Sound waves are a physical phenomenon that plays a crucial role in various aspects of everyday life, ranging from communication to the arts. This community service aims to enhance the understanding of the public, particularly in Pulau Tidung, regarding the basic concepts of sound waves and their applications. Through a series of activities including seminars, practical experiments, and creative projects, participants are invited to engage directly with the concept of sound waves. The results of the activities indicate an increase in participants' understanding of sound wave theory, as well as their ability to communicate and be creative. The projects produced, such as creating musical instruments from recycled materials, demonstrate active participation from the participants in the learning process. Additionally, this initiative has successfully strengthened social ties among community members. Thus, this service not only provides scientific knowledge but also fosters creativity and positive social interaction. The sustainability of this program is essential to ensure long-term impacts for the community.